Exploring Research Trends of Online Learning for Developing English Reading Skills: A Bibliometric Analysis - Dr. Prodhan Mahbub Ibna Seraj; Mohammad Hamidul Haque; Dr. Md. Asif Kamal (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Increasing research has demonstrated the importance of online reading for teaching and improving EFL students' reading abilities. However, there are few studies using bibliometrics to examine the literature and identify patterns in this field. This study aimed to identify significant trends within this field of research and to develop an intellectual overview of relevant scholarly work. Bibliographic data for 82 research publications published between 2008 and 2022 (February) were obtained from the Scopus database. Perish/publish, and the VOS viewer was used for data analysis. The publication trend was analyzed using bibliographic indicators, focusing on characteristics such as the most productive year, the top 10 most cited authors, document types, and prominent themes based on the frequently used keywords within the study area. The study's conclusions demonstrate that since 2017, the body of literature in this area has been continuously growing. However, during the COVID-19 epidemic in 2021, the number of research studies skyrocketed. Based on the findings of twenty studies, research was carried out on reading methods, the effects of online reading, and the distinctions between online and printed reading. In light of the aforementioned study, this paper concludes by attempting to outline some potential topics for further investigation.